Political systems and the distribution of power - Banton, Michal (ed.) (London, 1965)
Modern political anthropology began in 1940 with the first systematic comparative studies of how primitive societies maintained law and order. The focus was on government and the presence or absence of state institutions. Recently, interest has shifted to the study of power, to examining the manipulation of political relations, and to the task of elaborating a classification of governmental systems that will throw light on the important problems for research.
Keywords: Federal government